Optimalisasi Keuntungan Produksi Makanan Olahan Mie Mengunakan Metode Simpleks - Palahudin, Palahudin; Aura Ginta Setia; Siti Nadya Safira; Safira Seftiyani; Muhamad Nauval Ardani; Muhammad Fiqih (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
As competition in the processed food industry becomes increasingly fierce, it is important for producers to determine the optimal production combination to maximize profits. This study aims to determine whether the products produced can provide maximum profit from noodle sales and to determine what variables inhibit the optimum value in the noodle processed product business so that mathematical modeling can be made using the simplex method linear program. Processed noodle products are businesses engaged in the culinary field, namely food made from various ingredients, with the main ingredients of tapioca flour and wheat flour. only the basic ingredients are different. As for complementary ingredients such as sauces and spices, it becomes a problem if one of these ingredients is not met, then production in the noodle business will be hampered. The results of the study show that the strategy that can be applied by producers is to ensure a sustainable supply of complementary ingredients, optimize the use of main raw materials, and prioritize products with the highest profit margins.